Investigation of M1 transitions of the ground-state configuration of In-like tungsten. (5th May 2016) - Li, W; Xiao, J; Shi, Z; Fei, Z; Zhao, R; Brage, T; Huldt, S; Hutton, R; Zou, Y
Abstract: Three visible lines of M1 transitions from In-like tungsten were recorded using the Shanghai Permanent Magnet Electron Beam Ion Trap. The experimental wavelengths were measured as 493.84 ± 0.15, 226.97 ± 0.13 and 587.63 ± 0.23 nm (vacuum wavelengths). These results are in good agreement with theoretical predictions obtained using the large-scale relativistic many-body perturbation theory, in the form of the flexible atomic code.